Carbon source requirements for mating and mating‐type switching in the methylotrophic yeasts Ogataea (Hansenula) polymorpha and Komagataella phaffii (Pichia pastoris). Issue 2 (6th January 2020) - Feng, Dahao; Stoyanov, Anton; Olliff, Juliana C.; Wolfe, Kenneth H.; Lahtchev, Kantcho; Hanson, Sara J.
Abstract: The methylotrophic yeasts Ogataea (Hansenula) polymorpha and Komagataella phaffii (Pichia pastoris) have important industrial applications and are models for several biological processes including peroxisome biology and methanol metabolism. We examined the carbon source requirements for mating‐type ( MAT ) switching and mating in both species. Haploid strains of O. polymorpha and K. phaffii are homothallic, and switch MAT by a flip/flop mechanism in which a chromosomal region containing the MAT genes undergoes an inversion. MAT switching is induced by nitrogen starvation in both species and can be detected 4–6 hr after induction. Both switching and mating require a utilizable carbon source that can be either fermentable or nonfermentable. We further observed that although methanol can be used as a sole carbon source in both species, it does not support the induction of MAT switching or mating. Our results provide insight into the nutritional cues that influence entry into sexual processes in methylotrophic yeasts that undergo flip/flop MAT switching.